2021
DOI: 10.5937/fme2101244n
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wind energy potential of the state of Tamil Nadu, India based on trend analysis

Abstract: An accurate estimate of wind resource assessment is essential for the identification of potential site for wind farm development. The hourly average wind speed measured at 50 m above ground level over a period of 39 years (1980-2018) from 25 locations in Tamil Nadu, India have been used in this study. The annual and seasonal wind speed trends are analyzed using linear and Mann-Kendall statistical methods. The annual energy yield, and net capacity factor are obtained for the chosen wind turbine with 2 Mega Watt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In concern with making the world better for the future, the research works in civil engineering have shared immense contributions in various domains of science, engineering and technology (Parkin 2000;Babu et al 2017). However, despite challenges in balancing the carbon emission in the construction industry, various sustainable materials and practices have been evolving throughout the globe leading towards a systematic plan for smart and sustainable infrastructure development with a circular economy business models (Rehman et al 2020;Natarajan et al 2021). As a result, the practices and policies related to environmental pollution control and cleaning technologies have been receiving wide attention as part of the sustainable development goals (Ruggerio 2021).…”
Section: Department Of Civil Engineering Hindustan Institute Of Techn...mentioning
confidence: 99%
“…In concern with making the world better for the future, the research works in civil engineering have shared immense contributions in various domains of science, engineering and technology (Parkin 2000;Babu et al 2017). However, despite challenges in balancing the carbon emission in the construction industry, various sustainable materials and practices have been evolving throughout the globe leading towards a systematic plan for smart and sustainable infrastructure development with a circular economy business models (Rehman et al 2020;Natarajan et al 2021). As a result, the practices and policies related to environmental pollution control and cleaning technologies have been receiving wide attention as part of the sustainable development goals (Ruggerio 2021).…”
Section: Department Of Civil Engineering Hindustan Institute Of Techn...mentioning
confidence: 99%
“…The utilization of RES is being encouraged in a wide range of applications, such as quality power supply to isolated and small applications through hybrid power systems [1][2][3][4][5], offgrid and grid-connected wind and solar the adverse effects of conventional energy sources. The utilization of RES is being encouraged in a wide range of applications, such as quality power supply to isolated and small applications through hybrid power systems [1][2][3][4][5], offgrid and grid-connected wind and solar PV farms [6][7][8][9][10][11][12][13], power generation using the solar chimney concept [14], аnd sоlаr аir соnditiоning аnd desalination [15][16][17]. With technological advancement and commercial acceptance of RES and new energy industries, the demand for energy storage systems is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the two leading dynamic issues in masts design are the extreme movement at the top of the tower and the fatigue of welded elements. Besides, many countries [2,3] have investigated wind energy potential and optimal locations of wind turbines.…”
Section: Introductionmentioning
confidence: 99%